Analisis Variabel Yang Mempengaruhi Loyalitas Pengguna Muamalat Digital Islamic Network di Kota Madiun - ari rahmat sugara; Tati Handayani (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
This study aims to identify and explain the variables that influence the loyalty of Muamalat Digital Islamic Network users in Madiun City. Quantitative method is the method used in this study. The population in this study is the Muamalat Digital Islamic Network user community in Madiun. This study uses primary data as a data source with a purposive sampling method of 175 respondents and data collection techniques using a questionnaire. The data analysis technique in this study is the inner model and outer model using SmartPLS. This study explains that the level of knowledge has a significant effect on loyalty. The level of knowledge is important because the respondents' answers indicate that customers know how to create an account either through the Muamalat DIN application or through Bank Muamalat KCP Madiun by coming in person. There is a significant effect of the satisfaction variable on customer loyalty. Satisfaction is obtained through customers who are comfortable when transacting using Muamalat DIN. The trust variable has a significant influence on loyalty. Customers believe that the safety of their deposit funds in Bank Muamalat has been guaranteed.